Antibiogram of Urinary Escherichia coli isolated in Sir Salimullah Medical College Mitford Hospital, Dhaka. (Bangladesh Journal of Medical Microbiology, 2013)
Urinary tract infections (UTIs) are one of the most common infectious diseases & an important cause of morbidity in general population. More than 90% of all uncomplicated UTI s are caused by Esch. coli infection. The study was carried out in Department of Microbiology of Sir Salimullah Medical College & Mitford Hospital (SSMC& MH) Dhaka from October 2002 to September 2003. A total of 749 urine samples were studied of which 414 (55.27) showed significant growth. Among the 414 isolates, E sch. coli was the most predominant (82.61%) organism. Esch. coli was highly sensitive to Imipenem (95.02%) followed by Ceftriaxone (86.84%), Cefuroxime (67.54%), Gentamicin (66.08%), and Ceftazidime (55.84%) respectively. Low sensitivity patterns were shown against Nitrofurantoin (44.73%) & Ciprofloxacin (40.64%). The sensitivity to other antibiotics varied from 23.39% to as low as 2.63%. The aim of the present study was to observe the antibiotic sensitivity pattern of isolated Esch. coli from urine samples of patients admitted in inpatient department or visited the out patient department of Sir Salimullah Medical College & Mitford Hospital (SSMC& MH) Dhaka.DOI: http://dx.doi.org/10.3329/bjmm.v5i2.16934 Bangladesh J Med Microbiol 2011; 05 (02): 23-26